2017
DOI: 10.1097/cin.0000000000000363
|View full text |Cite
|
Sign up to set email alerts
|

Using Quick Response Codes in the Classroom

Abstract: With smart device technology emerging, educators are challenged with redesigning teaching strategies using technology to allow students to participate dynamically and provide immediate answers. To facilitate integration of technology and to actively engage students, quick response codes were included in a medical surgical lecture. Quick response codes are two-dimensional square patterns that enable the coding or storage of more than 7000 characters that can be accessed via a quick response code scanning applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…The key benefits of using QR codes for healthcare education lie in the ability to provide timely, multimodal information in a cost-effective manner. Several studies demonstrated an improvement in engagement from students or faculty [19,20,22,23,26,[39][40][41][42], which may be due to ease of use, availability and immediacy compared to other available methods of accessing information. Additional benefits lie in adaptability, simplicity of creation and potential environmental benefits of QR codes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The key benefits of using QR codes for healthcare education lie in the ability to provide timely, multimodal information in a cost-effective manner. Several studies demonstrated an improvement in engagement from students or faculty [19,20,22,23,26,[39][40][41][42], which may be due to ease of use, availability and immediacy compared to other available methods of accessing information. Additional benefits lie in adaptability, simplicity of creation and potential environmental benefits of QR codes.…”
Section: Discussionmentioning
confidence: 99%
“…Nine articles discussed ways in which QR codes could be utilised to enhance participant engagement [19][20][21][22][23][24][25][26][27]. These can be broadly divided into those focusing on anatomy teaching, formative assessment, case-based learning and engagement with publications.…”
Section: Theme 1: Increasing Participant Engagementmentioning
confidence: 99%
See 2 more Smart Citations
“…The main uses of QR codes in healthcare education emerging from thematic analysis were as follows: Nine articles discussed ways in which QR codes could be utilised to enhance participant engagement [19][20][21][22][23][24][25][26][27]. This can be broadly divided into those focusing on anatomy teaching, formative assessment, case-based learning and engagement with publications.…”
Section: Article Characteristicsmentioning
confidence: 99%